2019
DOI: 10.9744/jmk.21.2.120-129
|View full text |Cite
|
Sign up to set email alerts
|

THE INTENDED USE OF FUNDS AND IPOs MARKET PERFORMANCE IN INDONESIAN CAPITAL MARKET

Abstract: Specific information on the IPO prospectus can affect the stock's market performance, both the initial returns and the long-term performance. The disclosure of the purpose of IPO proceeds to: acquisition, investment, group financing, debt repayment and working capital, as a specific form of information is indicated to affect both initial return and long-term stock returns. We conducted a test of 148 IPOs on the Indonesia Stock Exchange in the period 2006-2013. Data analysis was performed using OLS and probit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Balatbat and Bertinshaw (2008) researched 174 Australian IPOs and discovered that it was extremely relevant when making investment decisions. Meidiaswati et al (2019) reported that using proceeds related to the performance of IPOs in the Indonesian market is also utilized during decision-making concerning investment. Leone et al (2006) and Balatbat and Bertinshaw (2008) reported that the use of funds caused a decline in information asymmetry among issuers (managers) and third parties such as investors and other fund providers.…”
Section: Introductionmentioning
confidence: 99%
“…Balatbat and Bertinshaw (2008) researched 174 Australian IPOs and discovered that it was extremely relevant when making investment decisions. Meidiaswati et al (2019) reported that using proceeds related to the performance of IPOs in the Indonesian market is also utilized during decision-making concerning investment. Leone et al (2006) and Balatbat and Bertinshaw (2008) reported that the use of funds caused a decline in information asymmetry among issuers (managers) and third parties such as investors and other fund providers.…”
Section: Introductionmentioning
confidence: 99%